Hydrogeochemical studies of ground waters in Neyveli basin along the Cuddalore coast, SE coast of India - Senthil, Kumar G.; Ramanathan, A. L.; Chidambaram, S.; Prasanna, Mohan Viswanathan (CUTSE 2009, 2009)
A detailed study had been carried out on groundwater in Neyveli basin along the Cuddalore coast to establish the hydrogeochemistry and identify the various sources of contaminants as well assess the physical and chemical quality of the groundwater. The groundwater was found to vary considerably in terms of chemical and physical properties. Generally the water was alkaline, high chemical constituents near the coastal region and undersaturated with respect to carbonate minerals. The majority of groundwater clustered towards Mg-Cl, Ca-Cl and Na-Cl facies. Interpretation of data reveals that weathering and ion exchange through which major ions enter the groundwater system. Anthropogenic activities were found to have greatly impacted negatively on the quality of the groundwater.